Stages of development of the lean production concept and special features of its adaptation to the national economy - Kolos, Irina; Grechan, Alla (My University, 2016)
Features for territorial and chronological changes in the orientations of the concept of lean production argued. Achievements of the world auto industry leaders in lean improvements that ensure adoption of lean thinking and lean culture are represented. The feasibility of the introduction of company management on the principles of lean is proved taking into account peculiarities of the national economy through the prism of public-private partnership: public institutions, social organizations, top management of companies and stakeholders (primarily suppliers and customers). It was discovered that search for ways to overcome the external imbalances contributes to the development of partnerships at different levels: regional, national, supranational and global. The conclusion is made that the state support is crucial for the dissemination of the concept of lean production. Experience for the introduction of elements of the concept and implementation of the tools of lean production at domestic enterprises, which confirms the effectiveness and appropriateness of active implementation is considered.
Keywords: кафедра обліку і аудиту; ощадливе виробництво; lean production